Inhibition of human thymidine phosphorylase by conformationally constrained pyrimidine nucleoside phosphonic acids and their "open-structure" isosteres - Košiová, Ivana; Šimák, Ondřej; Panova, Natalya; Buděšínský, Miloš; Petrová, Magdalena; Rejman, Dominik; Liboska, Radek; Páv, Ondřej; Rosenberg, Ivan (European journal of medicinal chemistry, 2014)
A series of conformationally constrained uridine-based nucleoside phosphonic acids containing annealed 1,3-dioxolane and 1,4-dioxane rings and their "open-structure" isosteres were synthesized and evaluated as potential multisubstrate-like inhibitors of the human recombinant thymidine phosphorylase (TP, EC 2.4.2.4) and TP obtained from peripheral blood mononuclear cells (PBMC). From a large set of tested nucleoside phosphonic acids, several potent compounds were identified that exhibited Ki values in the range of 0.048-1 μM. The inhibition potency of the studied compounds strongly depended on the degree of conformational flexibility of the phosphonate moiety, the stereochemical arrangement of the sugar-phosphonate component, and the substituent at position 5 of the pyrimidine nucleobase.
Keywords: molekulární konformace; pyrimidinové nukleosidy; Pyrimidine Nucleosides; kyseliny fosforité; Thymidine Phosphorylase; Phosphorous Acids; Humans; lidé; Molecular Conformation; Enzyme Inhibitors; vztahy mezi strukturou a aktivitou; inhibitory enzymů; thymidinfosforylasa; Structure-Activity Relationship